Study Designs and Systematic Reviews of Interventions: Building Evidence Across Study Designs. (June 2014) - Sargeant, J. M.; Kelton, D. F.; O'Connor, A. M.
Summary: This article is the second article in a series of six focusing on systematic reviews in animal agriculture and veterinary medicine. This article addresses the strengths and limitations of study designs commonly used in animal agriculture and veterinary research to assess interventions (preventive or therapeutic treatments) and discusses the appropriateness of their use in systematic reviews of interventions. Different study designs provide different evidentiary value for addressing questions about the efficacy of interventions. Experimental study designs range from in vivo proof of concept experiments to randomized controlled trials (RCTs) under real‐world conditions. The key characteristic of experimental design in intervention studies is that the investigator controls the allocation of individuals or groups to different intervention strategies. The RCT is considered the gold standard for evaluating the efficacy of interventions and, if there are well‐executed RCTs available for inclusion in a systematic review, that review may be restricted to only this design. In some instances, RCTs may not be feasible or ethical to perform, and there are fewer RCTs published in the veterinary literature compared to the human healthcare literature. Therefore, observational study designs, where the investigator does not control intervention allocation, may provide the only available evidence of intervention efficacy. While observational studies tend to be relevant to real‐world use of an intervention, they are more prone to bias. Human healthcare researchers use a pyramid of evidence diagram to describe the evidentiary value of different study designs for assessing interventions. Modifications for veterinary medicine are presented in this article.